IPLR: an online resource for Greek word-level and sublexical information. - Protopapas, Athanassios; Tzakosta, Marina; Chalamandaris, Aimilios; Tsiakoulis, Pirros (Language Resources & Evaluation, 2012)
We present a new online psycholinguistic resource for Greek based on analyses of written corpora combined with text processing technologies developed at the Institute for Language & Speech Processing (ILSP), Greece. The 'ILSP PsychoLinguistic Resource' (IPLR) is a freely accessible service via a dedicated web page, at . IPLR provides analyses of user-submitted letter strings (words and nonwords) as well as frequency tables for important units and conditions such as syllables, bigrams, and neighbors, calculated over two word lists based on printed text corpora and their phonetic transcription. Online tools allow retrieval of words matching user-specified orthographic or phonetic patterns. All results and processing code (in the Python programming language) are freely available for noncommercial educational or research use.